Open access case study: how is the situation in vet research in Germany? : questions and perspectives - Rödel, Bodo [Verfasser] (Bundesinstitut für Berufsbildung, 2018)
With regard to access to data and academic results, one important element is open accessibility of academic research publications: Open Access. This specialist Internet article provides a fundamental explanation of the Open Access concept. Furthermore, the developments concerning Open Access in vocational education and training research in Germany are explained. (BIBB-Doku)
Keywords: G 2.2 Informations- / Wissensgesellschaft; Berufsbildungsforschung; Open Access; Elektronisches Publizieren; Forschungsprojekt